A study of the genus Aphelocheirus (Hemiptera: Nepomorpha: Aphelocheiridae) from northern Vietnam, with descriptions of three new species - Tran, A.d.; Nguyen, X.q. (Zootaxa, 2016)
Three new species, Aphelocheirus (s.str.) apicalis sp.n., A. (s.str.) flavinotatus sp.n., and A. (s.str.) sapa, sp.n. are described from northern Vietnam. Aphelocheirus (s.str.) lahu Polhemus & Polhemus, 1988 is reported from Vietnam for the first time. Additional distribution records of A. (s.str.) gularis Horváth, 1918 and A. (s.str.) inops Horváth, 1918 are provided.